Son of God: divine sonship in Jewish and Christian antiquity - Allen, Garrick V.; Akagi, Kai; Sloan, Paul T.; Nevader, Madhavi (Penn State University Press, 2021)
Frontmatter -- Contents -- Abbreviations -- Introducing Son of God : Divine Sonship in Jewish and Christian Antiquity -- Part I: Son of God in Early Jewish Literature -- 1. Son of God and Son of Man: 4Q246 in the Light of the Book of Daniel -- 2. Son of God, Sons of God, and Election in the Dead Sea Scrolls -- 3. Son of God in Wisdom 2:16–18: Between the Hebrew Bible and the New Testament -- 4. Son of God in the Book of Revelation and Apocalyptic Literature -- 5. Whose Son Is the Messiah? -- Part II: Son of God in Early Christianity and the Gentile World -- 6. Jesus’s Use of “Father” and Disuse of “Lord” -- 7. “Whoever Does the Will of God” (Mark 3:35): Mark’s Christ as the Model Son -- 8. Son of God and Christian Origins -- 9. Son of God in Gentile Contexts (That Is, Almost Everywhere) -- 10. “Declared to Be Son of God in Power”: Romans 1:4 and the Iconography of Imperial Apotheosis -- 11. “To Become like His Brothers”: Divine Sonship and Siblingship in Hebrews -- 12. Son(s) of God: Israel and Christ: A Study of Transformation, Adaptation, and Rivalry -- 13. What Does God Get Out of It? Reciprocity and Divine Sonship -- Bibliography -- Contributors -- Index of Ancient Sources